Lexical Bundles in Thai Medical Research Articles - Panthong, Panupan; Poonpon, Kornwipa (Journal of Studies in the English Language, 2020)
Lexical bundles, co-occurred words serving as the building block facilitating communication, have been a focus in studies of academic written English for decades. Nonetheless, few studies highlighted this topic in academic writing for specific purposes. This research study aimed to investigate lexical bundles used in medical research articles published in the highest rank and to analyze their structure and functions. A corpus of 346 medical research articles was collected from the highest ranked medical journal published in Thailand. Thai Med corpus consists of 801,052 tokens. AntConc software program, N- Grams function, was used to identify four lexical bundles. An analysis of structures and functions of these lexical bundles was conducted, using a framework adapted from Biber, Conrad and Cortes (2004) and Hyland (2008a). The result revealed 76 salient lexical bundles in the corpus. Structurally, prepositional phases and noun phrases are most frequently used. Functionally, the lexical bundles were most highly used for research-oriented function, followed by text-oriented, while no bundles were used for participant-orientation. The study indicated that lexical bundles produced by Thai medical researchers were not extensive and varied and that the occurring lexical bundles are related to discourse community.